A multiscale model for optimizing the flexural capacity of FRC structural elements. (1st November 2020) - Nonato Da Silva, C.A.; Ciambella, J.; Barros, J.A.O.; dos Santos Valente, T.D.; Costa, I.G.
Abstract: In the present work, a multiscale model for fibre reinforced concrete (FRC) beams failing in bending is presented. At the microstructural level, the fibre is modelled as a one-dimensional continuum with axial, shear and bending deformability, with cohesive-like interfaces to simulate the interaction with the surrounding concrete. At the macroscopic level, the response of the beam is simulated by discretising the cross-section into layers and by enforcing the proper compatibility conditions between the layers. In the post-cracking stage, the tensile capacity is assured by the fracture energy of the concrete and the fibre resisting mechanisms simulated by the fibre pull-out constitutive laws determined at the microstructural level. The model can account for fibre distribution and orientation, controlled by the casting conditions and geometry of the mould. By using experimental data available from the open literature, it is proved that such an integrated approach is able to derive, by inverse analysis, the stress-crack width relationship of FRC, which is the fracture mode I information in the material nonlinear analysis of FRC structures with approaches based on the finite element method.